Comparison of Outcomes Frozen Shoulder Treatment with Physiotherapy Alone Versus Physiotherapy Intraarticular Injection - Sohban, Muhammad Usman (Indus Journal of Bioscience Research, 2025)
Background: Frozen shoulder, or adhesive capsulitis, is a common cause of shoulder pain and stiffness, often resulting in significant functional impairment. Objective: To compare the clinical outcomes of frozen shoulder treatment using physiotherapy alone versus physiotherapy combined with intra-articular corticosteroid injection over a six-week period. Methods: This randomized controlled trial was conducted at the Orthopedic Department of Bahawal Victoria Hospital, Bahawalpur from 07 November 2024 to 06 April 2025. A total of 82 patients diagnosed with frozen shoulder were enrolled and randomly assigned into two equal groups (n=41 each). Group A received an intra-articular corticosteroid injection (80 mg triamcinolone acetonide with 2% xylocaine) along with physiotherapy. Group B received physiotherapy alone. Both groups underwent 10 physiotherapy sessions including TENS, active range of motion exercises, and ice application. Results: At six weeks, Group A demonstrated a significantly greater reduction in SPADI scores (mean: 35.2 ± 5.4) compared to Group B (mean: 41.8 ± 6.0) with a p-value of 0.001. Additionally, 82.9% of patients in Group A achieved more than 30% improvement in SPADI scores compared to 61.0% in Group B (p = 0.015). Stratified analysis confirmed consistent improvements across age, gender, and duration subgroups. Minimal adverse effects were reported, with no serious complications in either group. Conclusion: It is concluded that the combination of intra-articular corticosteroid injection and physiotherapy is more effective than physiotherapy alone in the short-term treatment of frozen shoulder. This approach provides faster pain relief and improved functional outcomes with good safety and tolerability.